2020
DOI: 10.1177/1089253220960894
|View full text |Cite
|
Sign up to set email alerts
|

Venous Waveform Analysis Correlates With Echocardiography in Detecting Hypovolemia in a Rat Hemorrhage Model

Abstract: Background Assessing intravascular hypovolemia due to hemorrhage remains a clinical challenge. Central venous pressure (CVP) remains a commonly used monitor in surgical and intensive care settings for evaluating blood loss, despite well-described pitfalls of static pressure measurements. The authors investigated an alternative to CVP, intravenous waveform analysis (IVA) as a method for detecting blood loss and examined its correlation with echocardiography. Methods Seven anesthetized, spontaneously breathing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Significance for all ANOVA analysis was set at P < .05 (2-tailed), while significance for the pairwise difference in R 2 was set as the 95% CI not crossing Sample size analysis was calculated to detect a significant change in F1 with hemorrhage of 2% of the EBV. Based on study by Lefevre et al 20 who saw a reduction in F1 mean of 0.28 with hemorrhage of 6% of the EBV, we assumed a linear response when detecting 2% hemorrhage and thus anticipated a change in mean F1 of 0.93 and standard deviation of 0.1. 1 To allow adequate power of 0.8, allowing type 1 error of 0.05, in a continuous variable from a matched pairs study using a t test, would require 11 subjects to reject the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Significance for all ANOVA analysis was set at P < .05 (2-tailed), while significance for the pairwise difference in R 2 was set as the 95% CI not crossing Sample size analysis was calculated to detect a significant change in F1 with hemorrhage of 2% of the EBV. Based on study by Lefevre et al 20 who saw a reduction in F1 mean of 0.28 with hemorrhage of 6% of the EBV, we assumed a linear response when detecting 2% hemorrhage and thus anticipated a change in mean F1 of 0.93 and standard deviation of 0.1. 1 To allow adequate power of 0.8, allowing type 1 error of 0.05, in a continuous variable from a matched pairs study using a t test, would require 11 subjects to reject the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, notable advances in signal processing and machine learning (ML) have fostered the application of these techniques in hypovolemia diagnosis. Representative examples include discrete Fourier transform-based analysis of arterial blood pressure waveform [ 13 ], fast Fourier transform-based analysis of central venous blood pressure waveform [ 14 ], ML analysis of arterial blood pressure waveform in its entirety (known as “Compensatory Reserve Index”) [ 15 ], support vector machine analysis of compressed arterial blood pressure waveform via principal components analysis [ 16 ], ML analysis of photoplethysmogram (PPG) signal features derived from time-frequency analysis [ 17 ], deep learning analysis of electronic medical records, vital signs, and laboratory values [ 18 , 19 ], and natural language processing-aided voting ensemble ML analysis of pulse pressure and unstructured clinical notes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lefevre et al 1 in their basic science study of hemorrhagic shock in rat model demonstrated that intravenous waveform analysis obtained from fast Fourier transform analysis and fundamental frequency amplitude was superior to central venous pressure measurement, and also correlated well with left ventricular end-diastolic area and mean arterial pressure. Hemorrhagic shock experimental models are mainly 4 types, a fixed-pressure, a fixed-volume, a controlled hemorrhage, and an uncontrolled hemorrhage models.…”
mentioning
confidence: 99%